Association between tirofiban monotherapy and efficacy and safety in acute ischemic stroke - Chunrong Tao; Yuyou Zhu; Chao Zhang; Jianlong Song; Tianlong Liu; Xiaodong Yuan; Wenwu Luo; Changchun Chen; Dezhi Liu; Yuanyuan Zhu; Jie Liu; Wei Hu (BMC Neurology, 2021)
Abstract Background Studies have suggested that glycoprotein IIb/IIIa antagonists such as tirofiban are beneficial for patients with acute coronary syndromes. However, it is still uncertain about the efficacy and safety of tirofiban in patients with acute ischemic stroke (AIS). Methods In this prospective non-randomized study, 255 AIS patients were recruited from 4 comprehensive stroke centers in China between January, 2017 and May, 2018. Among them,169 patients were treated with aspirin plus clopidogrel and 86 patients were treated with tirofiban. The primary functional outcome was the distribution of the 90 days’ modified Rankin Scale (mRS). The safety outcomes included the incidence of intracranial hemorrhage (ICH) at discharge and mortality at 3 months. Results In the propensity score matched cohort, tirofiban alone was noninferior to the dual antiplatelet with regard to the primary outcome (adjusted common odds ratio, 0.97; 95% confidence interval, 0.46 to 2.04; P = 0.93). Mortality at 90 days was 10% in the dual antiplatelet group and 8% in the tirofiban group (adjusted odds ratio 0.75; 95% CI 0.08 to 7.40, p = 0.81). There was no difference of the ICH rate between two groups (adjusted odds ratio 0.44; 95% CI 0.13 to 1.48, p = 0.18). In the inverse probability of treatment weighting-propensity score-adjusted cohort, similar differences were found for functional and safety outcomes. Conclusions Our study suggested that tirofiban use appears to be safe as monotherapy in AIS treatment compared with common dual antiplatelet therapy, however, no improvement in functional outcomes was found. Trial registration Chinese clinical trial registry, ChiCTR2000034443 , 05/07/2020. Retrospectively registered.